Sociedade de Matemática de São Paulo: um estudo histórico-institucional - Trivizoli, Lucieli Maria [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
A intenção neste trabalho é contribuir para as investigações da História da Matemática no Brasil focalizando uma instituição e sua produção científica. Tratase de um estudo a respeito da Sociedade de Matemática de São Paulo, que foi fundada em 1945 e dissolvida em 1972, uma vez que ela passava por dificuldades financeiras e seus membros seriam incorporados por uma nova sociedade de âmbito nacional. Tem-se a finalidade de identificar a importância dessa instituição para o desenvolvimento e organização da Matemática e da comunidade matemática no Brasil, bem como apontar as pessoas fundamentais na criação dessa Sociedade e em sua organização. O trabalho traz, ainda, um estudo sobre o periódico oficial da referida sociedade, denominado Boletim da Sociedade de Matemática de São Paulo, que compreende 77 artigos distribuídos na coleção constituída por 18 volumes, publicados entre 1946 e 1966. A partir da criação dessa Sociedade, é possível perceber os sinais da organização de uma comunidade matemática brasileira preocupada com a melhoria da qualidade da produção matemática no país, com o objetivo de publicar e divulgar os resultados obtidos nas pesquisas brasileiras. Com este estudo, espera-se reconhecer a importância dessa Sociedade para o desenvolvimento e institucionalização da Matemática no Brasil.

The aim of this work is to contribute to the investigation of History of Mathematics in Brazil, focusing on a Brazilian institution and its scientific production. This is a study of the Society of Mathematics of São Paulo, which was founded in 1945 and dissolved in 1972, as it was going through some financial troubles and its members would be covered by a new society with national coverage. It is aimed to identify the importance of this institution for the development and organization of Mathematics and of the mathematical community in Brazil, as well as to point out fundamental people in the creation of this society and in its organization. Moreover, this work brings up a study of the official journal of the Society, called Bulletin of the Society of Mathematics of São Paulo, which has got about 77 articles distributed throughout this collection, divided into 18 volumes, published from 1946until 1966. Paying attention to the creation of this Society, it is possible to realize the signs of an organization of a Brazilian mathematical community concerned about improving the quality of mathematical production in the country with the goal of publishing and spreading the results obtained in Brazilian researches. With this study, it is expected to recognize the importance of that Society for the development and institutionalization of Mathematics in Brazil.
Keywords: Matematica - Historiografia; Matemática - História - Brasil; Matemática - Sociedades, etc; Sociedade de Matemática de São Paulo; Instituições; Society of Mathematics of São Paulo; History of Mathematics in Brazil; Mathematical Historiography; Institutions